ANALISIS PENDAPATAN, DAYA SAING DAN DAMPAK KEBIJAKAN USAHA TANI LADA (Piper nigrum. L) DI KABUPATEN WAYKANAN - radenusman r.adat; Wan Abas Zakaria; Dwi Haryono (Universitas Muhammadiyah Kotabumi, 2023)
Abstract,This study aims to analyze income, analyze competitiveness and determine the impact of policies on income and competitiveness of pepper farming in Way Kanan Regency. The research was conducted in Way Kanan District, GunungLabuhan District and Kasui District. The location was chosen purposively with the consideration that the area is a pepper production center in Way Kanan Regency. Sampling of farmers was carried out using the census method with a total of 80 pepper farmers as respondents. The analytical tool used to analyze income, competitiveness and the impact of pepper farming policies in Way Kanan Regency uses the PAM method. The results of the analysis obtained from the research conducted are the highest private/financial income from the exploitation of black pepper in Way Kanan Regency in the 10th year of IDR 32,426,467.70/ha. The largest social/economic income in the 10th year of production is IDR 126,709,367.67/ha. Pepper farming in Way Kanan Regency has a competitive advantage and a comparative advantage with PCR (Private Cost Ratio) and DRCR (Domestic Resource Cost Ratio) values of 0.9392 and 0.4713, respectively, so it is feasible and profitable to cultivate. The fertilizer subsidy policy can increase the income and competitiveness of the pepper commodity in Way Kanan Regency. Keywords: Competitiveness, Income and Pepper.